In vitro evaluation of the synergistic antioxidant and anti-inflammatory activities of the combined extracts from Malaysian Ganoderma lucidum and Egyptian Chlorella vulgaris - Marwa M. Abu-Serie; Noha H. Habashy; Wafaa E. Attia (BMC, 2018)
Abstract Background Since oxidative stress and inflammation are two linked factors in the pathogenesis of several human diseases. Thus identification of effective treatment is of great importance. Edible mushroom and microalgae are rich in the effective antioxidant phytochemicals. Hence, their beneficial effects on oxidative stress-associated inflammation are extremely required to be investigated. Methods This study evaluated the functional constituents, antioxidant and anti-inflammatory activities of Malaysian Ganoderma lucidum aqueous extract (GLE) and Egyptian Chlorella vulgaris ethanolic extract (CVE). Also, the synergistic, addictive or antagonistic activities of the combination between the two extracts (GLE-CVE) were studied. Expression of inducible nitric oxide synthase, cyclooxygenase-2, and nuclear factor-kappa B, as well as levels of nitric oxide, tumor necrosis factor (TNF)-α, lipid peroxidation, reduced glutathione and antioxidant enzymes were determined using in vitro model of lipopolysaccharide-stimulated white blood cells.